First reprocessing of Southern Hemisphere ADditional OZonesondes (SHADOZ) profile records (1998–2015): 1. Methodology and evaluation - Witte, Jacquelyn C.; Thompson, Anne M.; Smit, Herman G. J.; Fujiwara, Masatomo; Posny, Françoise; Coetzee, Gert J. R.; Northam, Edward T.; Johnson, Bryan J.; Sterling, Chance W.; Mohamad, Maznorizan; Ogino, Shin-Ya; Jordan, Allen; et al. (AGU, 2017)
Electrochemical concentration cell ozonesonde measurements are an important source of highly resolved vertical profiles of ozone (O₃) with long-term data records for deriving O₃ trends, model development, satellite validation, and air quality studies. Ozonesonde stations employ a range of operational and data processing procedures, metadata reporting, and instrument changes that have resulted in inhomogeneities within individual station data records. A major milestone is the first reprocessing of seven Southern Hemisphere ADditional OZonesondes (SHADOZ) station ozonesonde records to account for errors and biases in operating/processing procedures. Ascension Island, Hanoi, Irene, Kuala Lumpur, La Réunion, Natal, and Watukosek station records all show an overall increase in O₃ after reprocessing. Watukosek shows the largest increase of 9.0 ± 2.1 Dobson Units (DU) in total column O₃; Irene and Hanoi show a 5.5 ± 2.5 DU increase, while remaining sites show statistically insignificant enhancements. Negligible to modest O₃ enhancements are observed after reprocessing in the troposphere (up to 8%) and stratosphere (up to 6%), except at La Réunion for which the application of background currents reduces tropospheric O₃ (-2.1 ± 1.3 DU). Inhomogeneities due to ozonesonde/solution-type changes at Ascension, Natal, and La Réunion are resolved with the application of transfer functions. Comparisons with EP-TOMS, Aura's Ozone Monitoring Instrument and Microwave Limb Sounder (MLS) satellite O₃ overpasses show an overall improvement in agreement after reprocessing. Most reprocessed data sets show a significant reduction in biases with MLS at the ozone maximum region (50–10 hPa). Changes in radiosonde/ozonesonde system and nonstandard solution types can account for remaining discrepancies observed at several sites when compared to satellites.
Keywords: ozone; ozonesondes; SHADOZ; tropics